2012
DOI: 10.3346/jkms.2012.27.7.711
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic Effect of Glyphosate Mixture Containing Surfactants

Abstract: We investigated whether glyphosate influences the cellular toxicity of the surfactants TN-20 and LN-10 on the mouse fibroblast-like cells, alveolar epithelial cells, and a heart cell line. The cytotoxicity of TN-20 and LN-10 (0.4-100 µM), in the presence or absence of glyphosate was determined by assessing membrane integrity. TN-20 toxicity was significantly lower in the presence of 50 µM glyphosate for the fibroblast-like cell (6.25 µM; 3.9% ± 3.4% vs -4.8% ± 0.7%), for the alveolar cells (0.78 µM; 5.7% ± 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The contribution of surfactants to pesticide poisoning has been the focus of many recent studies Kim et al, 2013;Seok et al, 2011;Song et al, 2012a). Our previous work demonstrated that surfactants have toxic effects in cells, including disruption of cell membrane integrity and protein synthesis and alteration of metabolic and mitochondrial activities (Song et al, 2012b), with mitochondrial damage leading to apoptosis and necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of surfactants to pesticide poisoning has been the focus of many recent studies Kim et al, 2013;Seok et al, 2011;Song et al, 2012a). Our previous work demonstrated that surfactants have toxic effects in cells, including disruption of cell membrane integrity and protein synthesis and alteration of metabolic and mitochondrial activities (Song et al, 2012b), with mitochondrial damage leading to apoptosis and necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 2 patients (7.1%) had rhabdomyolysis (Tables 1 and 2). We have previously described the cell membrane toxicity of surfactants that are frequently included in pesticide formulations (20) and the synergistic toxicity between these surfactants and the actual herbicides (21). On the basis of these findings, we believe that the combined toxicity of surfactants and the chief pesticide ingredient is responsible for the high incidence of rhabdomyolysis in acute pesticide intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvants were always more toxic than the formulations, themselves always more than G. (Song et al, 2012) L-929 Fibroblasts, A549 Alveolar cells, Adjuvan ts / G 72h 0.066 -17…”
Section: Product Testedmentioning
confidence: 97%